Clinical Impression And Ultrasound Fealures In The Preoperative Evaluation Of Ovarian Masses - TSING,, CHEONG YEE (2001)
Main outcome measures The sensitivities, specificities, positive and negative predictive values of ultrasound features and clinical impression for discriminating a benign from a malignant ovarian mass. Results 120 constituted the study population after excluding 6 cases of non-ovarian pelvic pathology. 97 cases ( 81 % ) were diagnosed as benign ovarian tumours and 23 cases ( 19% ) as malignant. Clinical impression gave the highest level of sensitivity and specificity, followed by ultrasound score of 2-5 in the discrimination between benign and malignant ovarian masses. Both achieved sensitivity and specificity of greater than 700/0 and showed superiority over the individual ultrasound features suggestive of malignancy. Conclusions Clinical examination and ultrasound scanning are methods which can be applied easily in our centre in the preoperative evaluation of ovarian masses. The diagnostic accuracy may be improved by including tumour markers or more detailed ultrasound assessment, this would be at the expense of simplicity and increased financial cost.